Experimental study on the stability of the transmission tower with hybrid slab foundation. (1st May 2018) - Yuan, Guanglin; Yang, Biao; Huang, Zhaohui; Tan, Xiaozhe
Highlights: Conduct a test on the 1:5 scaled tower model of 220 kV power transmission tower with hybrid slab foundation. Investigate the stability of the tower subjected to horizontal ground surface motion. Generates a series of valuable test data on the behaviour of the tower. Compare the behaviour of the scaled tower model with different type foundations. Abstract: In this paper, a 1:5 scaled tower model for a typical 220 kV single-circuit power transmission tower with hybrid slab foundation has been designed and tested. The scaled tower model was tested under the movement of horizontal ground surface stretching with normal working loading conditions. One of the main objectives of this research is to investigate the stability of the power transmission tower subjected to horizontal ground movement by using hybrid slab foundation. The deformations of the tested tower model and stresses and strains within the different structural members of the tower and the reinforced concrete slab of the foundation have been fully measured. A large mount comprehensive test data has been generated. The research clearly indicated that compared to the isolated tower leg's foundation the proposed hybrid slab foundation has very good resistance, in terms of truss members' deformations and stresses, to the ground movement.